Why do we need an architectural approach to interoperability? - Bernd, Blobel; Oemig, Frank (European Journal for Biomedical Informatics, 2016)
Objectives: Health systems are on the move to increasing complexity, distribution, autonomy, number of domains or disciplines involved, thereby requesting evolution of interoperability to support required communication and cooperation among those systems for meeting intended business objectives. Methods: Information cycle model with its phases and phase transitions as well as systems theory are used to describe structure and processes of healthcare business cases and the interoperability levels for enabling the communication and cooperation between the principals involved. Results: When focusing on interoperability between health information systems acting as principals in an ICT business case, different levels of contribution to the common business case, i.e. phases to the completion of the information cycle, provided by the principals can be distinguished. While the first two levels, sharing data related to the business case, and sharing information derived from those data to define the required business process actions, deal with the communication challenge of interoperability, just the third level of providing the required action according to the business case concerns its operational part. Such service delivery requires appropriate system architecture for meeting the service functional cooperation challenge. When extending the consideration beyond ICT systems towards real world business systems, the architecture of non-ICT systems regarding their structure and behavior must be represented to be shared as required in the business case as well. This system extension requires domain knowledge based interoperability for covering the domain-specific concepts and relations including the constraints to be applied. When not just considering the domain-specific context, but also the context of the individual user, personalized business systems are managed. Conclusions: Advanced healthcare systems require not just communication standards for enabling interoperability, but also multi-domain, ontology-driven interoperability standards based on a generic reference architecture, that is also shortly presented in this paper.
Keywords: počítačové systémy; Computer Systems; Systems Integration; zdravotnické informační systémy; lékařská informatika; systémová integrace; mezioborová komunikace; Health Information Systems; Interdisciplinary Communication; Medical Informatics